Evidence of Kelvin-Helmholtz and tearing mode instabilities at the magnetopause during space weather events - Biasiotti, Lorenzo; Ivanovski, Stavro; Calderone, Lorenzo; Jerse, Giovanna; Laurenza, Monica; Del Moro, Dario; Longo, Francesco; Plainaki, Christina; Marcucci, Maria Federica; Milillo, Anna; Molinaro, Marco; Feruglio, Chiara (Frontiers in Astronomy and Space Sciences, 2024)
Kelvin-Helmholtz (KH) and tearing mode (TM) instabilities are one of the most important mechanisms of solar wind energy, momentum and plasma transport within the magnetosphere.To investigate the conditions under which KH-TM instabilities occur in the Earth environment it is fundamental to combine simultaneous multipoint in-situ measurements and MHD simulations. We analyzed data from the THEMIS and Cluster spacecraft considering two Space Weather (SWE) events starting with an M2.0 flare event (hereafter Case-1) that occurred on 21 June 2015 and the most-intensive flare (X9.3) of solar cycle 24 that occurred on 6 September 2017 (hereafter Case-2). Our analysis utilized a 2D MHD model for incompressible and viscous flow. The results from Case-1 indicate the presence of KH and TM instabilities, suggesting existence of observed low-amplitude oscillations at the nose of the magnetopause. However, the MHD simulations for Case-2 did not show any evidence of KH vortices, but did reveal the presence of "magnetic island" structures during a low-shear condition. The reconnection rate derived from the observations is compared with the computed one in the presence of developed instabilities inside the Earth's magnetopause.